2009
DOI: 10.2215/cjn.01260209
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulating Peritoneal Sclerosis in the New Millennium

Abstract: Background and objectives: The study aim was to establish the incidence and characterize all encapsulating peritoneal sclerosis (EPS) cases in patients treated by peritoneal dialysis (PD).Design Conclusions: The incidence reported in this study may be used to inform patients of the minimum risk of developing EPS on PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
207
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(223 citation statements)
references
References 32 publications
(47 reference statements)
12
207
4
Order By: Relevance
“…10 EPS is probably a multifactorial disease, in which PD duration represents an important risk factor. [11][12][13] Other conditions that have been inconsistently associated with EPS include cumulative glucose exposure, younger age, peritonitis episodes, b-blockers, and kidney transplantation. [11][12][13] Surprisingly, symptoms of EPS occur after PD withdrawal in most cases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10 EPS is probably a multifactorial disease, in which PD duration represents an important risk factor. [11][12][13] Other conditions that have been inconsistently associated with EPS include cumulative glucose exposure, younger age, peritonitis episodes, b-blockers, and kidney transplantation. [11][12][13] Surprisingly, symptoms of EPS occur after PD withdrawal in most cases.…”
mentioning
confidence: 99%
“…[11][12][13] Other conditions that have been inconsistently associated with EPS include cumulative glucose exposure, younger age, peritonitis episodes, b-blockers, and kidney transplantation. [11][12][13] Surprisingly, symptoms of EPS occur after PD withdrawal in most cases. [11][12][13] There are currently no definitive criteria that enable the detection of early stages of EPS.…”
mentioning
confidence: 99%
“…EPS is a rare but potentially devastating complication of PD (8). Recent large prospective cohort studies from Australia, New Zealand, and Scotland suggest that the 8-year cumulative incidence in patients undergoing PD ranges from 4% to 8% (9,10). Although peritoneal fibrosis is common in patients treated with PD, a diagnosis of EPS requires the clinical or radiologic/anatomic evidence for both peritoneal sclerosis and intestinal encapsulation (9).…”
Section: Discussion Of Questionmentioning
confidence: 99%
“…Recent large prospective cohort studies from Australia, New Zealand, and Scotland suggest that the 8-year cumulative incidence in patients undergoing PD ranges from 4% to 8% (9,10). Although peritoneal fibrosis is common in patients treated with PD, a diagnosis of EPS requires the clinical or radiologic/anatomic evidence for both peritoneal sclerosis and intestinal encapsulation (9). EPS should be diagnosed only in patients with suggestive clinical features with consistent radiologic or anatomic (intraoperative) findings.…”
Section: Discussion Of Questionmentioning
confidence: 99%
“…A Scottish study, also showed that the incidence of encapsulating peritonitis increases with time on PD 4 .…”
Section: Introductionmentioning
confidence: 92%